Planejamento racional por modelagem molecular, síntese e caracterização de glicosídeos com atividade inibitória potencial da acetilcolinesterase - Stefania Neiva Lavorato (2012)
Acetylcholinesterase (AChE) is the enzyme that catalyses the hydrolysis of the neurotransmitter acetylcholine, terminating synaptic cholinergic transmission. The use of AChE inhibitors have been associated with the improvement of the symptoms related to Alzheimers Disease and are the first choice drugs to treat the disease. The recent advances in the knowledge of the structure and function of AChE has inspired the search for new and more potent inhibitors, capable of binding to sites of the enzyme that are crucial to the pathology of the disease. Among the compounds already described as AChE inhibitors several are aryl glycosides. Thus, in view of the great need for more effective drugs for the symptomatic treatment and as disease-modifier, the aim of the present work was the rational design using molecular modeling, the synthesis and the biological evaluation of glycosides as potential AchE inhibitors. First, the virtual screening of a series of O- and S-glycosides bearing hydroxyl, amino or piperidino group at carbon-6 was performed by molecular docking. Twelve molecules were selected for synthesis. Two synthetic routes to these molecules were devised. All the selected compounds but one were obtained in yields ranging from 24 to 95%. Ten new compounds were prepared and characterized. According to the docking studies the S-glycosides showed the lower values of DGlig among the 6-hydroxy derivatives and that the replacement of the 6-hydroxyl group by amino or piperidino group enhances the interaction of the ligand with the enzyme.